Implementasi Model Rapid Application Development untuk Aplikasi Pelayanan Jasa Maintenance Pada PT. Dwi Tirtamas Tekhnik Karawang - Apriliah, Widya; Agrelia, Priska; Kurniawan, Ilham; Abdussomad, Abdussomad; Priska Agrelia (PROFITABILITAS, 2022)
Information is one of the important things that affect the development of business activities in the business sector, whether it's a service business or non-service, To realize this, currently in all aspects of the business field, there is no need to apply technology to produce information and support data processing in its business processes. In service, it also requires the support of an information system to facilitate data processing and effectiveness in providing services. At PT. Dwi Tirtamas The current technique requires an information system to be applied to maintenance service business activities to facilitate data processing, report presentation, information delivery and make it easier to provide maintenance services to customers. Therefore, in this research, an information system will be designed and built for maintenance services at PT. Dwi Tirtamas Karawang Technique. The software development model used in this study is the RAD (Rapid Application Development) model and the programming language for building an information system for maintenance services using the Java programming language.